Sexo e gênero em Galeno de Pérgamo: os cuidados de si e a geração do ser humano - Rubin, Luiza Batú (2024)
The objective of this research is to understand the vision of the Greek physician Galen of Pergamum (129- ca. 210 CE) regarding the body and gender elements present in his medical manuals, more specifically in books XIV and XV of the work On the Usefulness of the Parts of the Body or De usu partium, written between 164 and 175 EC, in which he describes the functions of the various parts and systems of the human body in addition to classifying the gender of men and women based on elements of their sexual body. We believe that Galen emphasizes special regimes of pleasure and self-care for each gender/sex, following determinations of his time, with the intention of indicating the best way to generate a human being, who would become the ideal citizen. We intend to address Galen's influences in philosophical and medical terms and, in particular, understand how such ideas circulated in his writing context, the end of the 2nd century CE. We will use the concept of gender to observe the categorizations made by Galen related to what would be masculine or feminine elements of Greco-Roman society based on his vision of the sexed body. We will limit our studies to a view historically located in the mid-2nd century, based on Galen's medical manuals, identifying the author and his ideas in their context, trajectory and philosophical influence